Technology of obtaining water-soluble surface-active substances by the method of phenol sulfomethylation - Sokolenko, Nadiia; Popov, Yevgeniy; Fastovetska, Kateryna (Eastern-European Journal of Enterprise Technologies, 2020)
The object of this study is a technology of the new surface-active substances (SAS) based on sulfomethylated phenol. The study's aim was to improve the technology by a catalytic method, implying the development of industrial schemes for the synthesis processes. During phenol sulfomethylation, the active conversion of monomers into polymeric substances starts only at a temperature of 110‒120 °C; the surface-active substances with an optimal polymeric composition were obtained only at a temperature of 130 °C. In the reaction of phenol sulfomethylation in a water environment at a temperature below 90 °C, obtaining SAS with the required properties takes more than 9 hours. The significant disadvantages of this technique are the relatively low yield of the target product and a significant amount of free phenol in the finished product (over 15 percent). It is known that a more powerful and less risky technique to accelerate the reaction than rising the temperature is catalysis. This study investigated the reaction of phenol sulfomethylation under conditions of interphase catalysis. This has made it possible to improve the main technological parameters: the reaction temperature was reduced from 130 °C to 90 °C, the process duration was shortened to 3 hours, to process was conducted at atmospheric pressure. The catalyst used was a cation-active SAS: cetyltrimethylammonium bromide. This makes it possible to simplify the technological scheme of obtaining SAS, that is, to use less energy-intensive and cheap reactors. A benefit of the proposed technology is the low-waste, single-stage production, and the use of available raw materials: phenol, formaldehyde, and sodium sulfite. During the study, the products were obtained that are similar, in terms of the surface-active properties, to the NF Dispersant, which is widely used in the industry. This makes it possible to expand the range of multifunctional surface-active substances with better bio destruction than products based on naphthalene and lignin. According to the results of studying the samples obtained, the scope of their application has been proposed. The resulting products have been tested, with positive results, as the anion-active SAS, used as dispersants in the production of organic dyes, as aligners when dyeing textiles, and as plasticizing additives for concrete mixtures